Principal's Leadership in Improving Teacher Performance at PAUD Tasdiiqul Insan - Lesmi, Kirana; Triono, Wahyu; Khotimah, Iim (Jurnal Edusci, 2025)
Background. Teacher performance refers to the provision of high- or low-quality education by an individual in the execution of their duties. The leadership of the Principal is expected to have the ability to move, influence, motivate, invite, direct, guide, govern, and nurture teachers, so that a high work ethic, creativity, and productivity in achieving goals is born. Purpose. The purpose of this study is to discuss how the leadership of the principal in PAUD Tasdiiqul Insan improves teacher performance. Method. This study uses a descriptive qualitative approach. The data collection method involves interview techniques, observation, and documentation. Result. The results of the study show that the principal's role in improving teacher performance in PAUD Tasdiiqul Insan encompasses multiple aspects, including educator, manager, administrator, supervisor, leader, innovator, and motivator. The steps taken by the principal to improve teacher performance at PAUD Tasdiiqul Insan include motivating teachers, enhancing teacher discipline, creating a conducive work environment, improving teacher competence, and enhancing academic competence. Conclusion. This study concludes that the principal's leadership in improving teacher performance at PAUD Tasdiiqul Insan is effective in carrying out his role as a principal. One of the steps taken by the principal to improve teacher performance is increasing teacher discipline, providing motivation, and offering gifts, but not in the form of monetary compensation. This is done to show appreciation, so that teachers are more motivated to improve their work performance. Implementation. Staff and infrastructure, as well as expert and teacher discipline, are supported by the spirit of the teacher himself and the motivation from the principal to the teachers